PNF as a Training System - Siff, M. C. (1999)
Strength training is often regarded as a discipline confined largely to the gymnasium or sports field. Unfortunately, this can obscure the fact that it can and does appear in other situations which have little direct connection with sport. In particular, PNF (Proprioceptive Neuromuscular Facilitation) contains many useful techniques which can play an important role in the strength training of athletes. It is one of the aims of this article to show that PNF is a comprehensive conditioning system which includes not only many of the principles already covered in the "Supertraining" book, but also adds insights which complement these principles. PNF is invariably regarded by conditioning coaches as a special type of sophisticated stretching, alongside static, ballistic and passive stretching. PNF is far more than just another stretching technique; it is actually an entire system of therapy comprising a broad spectrum of different techniques and procedures for rehabilitating patients suffering from various musculoskeletal injuries or disabilities. Stretching constitutes but one of many aspects of the full repertoire of PNF methods, yet even those enlightened coaches who use PNF extol only its virtues as a stretching system. Essentially, PNF recognizes that all physical conditioning depends primarily on neuromuscular processes involving sensitive receptors (proprioceptors) in the muscles, tendons and joints which enable a person to stabilise and move the body and its parts in space and time. Appropriate recruitment of the various stretch reflexes of the body, therefore, forms a vital part of PNF conditioning.